Pelaksanaan Pembagian Harta Bersama Setelah Adanya Putusan Hakim - Triwanto; Wicaksono, Pramuditya; Rahmat, Doris (Mitra Abdimas: Jurnal Pengabdian kepada Masyarakat, 2022)
The division of joint property in a divorce must indeed be carried out, but the husband and wife only question the distribution of the property after a court decision. This is because the husband and wife do not think about the treasures at all. And the problem that arises after the divorce is the problem of property going on. This study aims to examine the implementation of the distribution of joint property in the Religious Courts. The type of research used by the author is sociological juridical, the nature of qualitative descriptive research is research that describes events and behavioral interactions. Based on research and discussion, it is found that, the distribution of joint assets through the trial, can be done after a divorce, as described in Law number 7 of 1989 concerning the Religious Courts Article 86 paragraph (1). In deciding the case, the Panel of Judges uses a legal consideration, in which the decision has a strong legal basis which contains a legal abstraction that in the event of a divorce, each party (husband and wife) gets half of their joint property. If from the distribution of joint assets of husband and wife after the divorce, no agreement is found in the distribution, then this joint property becomes a dispute and the proof is through the trial process, with accurate evidence and witnesses.